Implementing Indicator Condition–Guided HIV Screening Alerts in the Emergency Department: Lessons Learned from a Case Study. - Fanjul, Francisco; Macià Romero, Maria Dolores; Fraile, Pablo; Guiu, Alexandra; Campins, Antoni; Ferré, Adrià; Pinecki, Sophia; Riera, Melchor (Inquiry (00469580), 2026)
Introduction: Indicator condition (IC)-guided HIV testing is recommended internationally as a cost-effective strategy but remains inconsistently implemented, particularly in emergency departments (EDs). Electronic health record (EHR) alerts may improve adherence; however, real-world uptake depends on organizational and specialty-level determinants. Methods: Prospective case study conducted between August 2023 and April 2025. A non-interruptive EHR alert was triggered by predefined IC-related laboratory orders and antimicrobial prescriptions. Crucially, the alert was only fired if HIV serology was not already requested, meaning that the accepted tests represented true additional screening. Clinicians could accept or decline testing with a single click. Acceptance patterns were analyzed by age group, clinical service, weekday versus weekend, and diurnal versus nocturnal shifts. The analysis employed descriptive stratification to evaluate confounding between patient age and clinical service volume. Results: Among 3,240 alert activations, 523 were accepted (16.1%), resulting in 398 completed tests. Eight patients tested positive (2.01%), including four actionable cases (1.01%). Two declined alerts were followed by subsequent diagnoses of advanced HIV infection. The apparent lower uptake in younger patients was service-level confounded by the concentration of alerts within gynecology/obstetrics (53.7% of all alerts in 18-37-year-olds; global gynecology uptake 3.5%). Outside gynecology, baseline acceptance was consistently higher (15-38%) across all age categories, demonstrating that the apparent age gradient was profoundly confounded by service distribution. Conclusion: Apparent age-related differences in alert uptake were attenuated after stratification by service distribution rather than intrinsic clinician bias regarding patient age. Specialty culture, workflow alignment, and ownership of preventive tasks appear to be central to the adoption of digital alerts in ED settings.